Research regarding to behavior on advanced plastic from rolling mills equipment. Issue 1 (January 2016) - Ardelean, M; Ardelean, E; Popa, E; Josan, A; Socalici, A
Abstract: New advanced plastic can be used in construction of different equipment's from some industries; due to mechanical properties closer to nonferrous materials. In steel industries uses of this materials are limited because working temperature is too low, related to nonferrous or ferrous material. In this paper is presented some researches related to replacement of bronze material with advanced plastic in construction of antifriction bearings. For replaces of this material with engineering plastic product, it was calculated analytical and using simulation, forces in node of braking mechanism. Using these loads, it was make simulation regarding behavior of static loads with finite element software. Based on these researches, this bearing can be made from engineering plastic product, in same qualitative and technical condition, and this is a way to reduce maintenance and exploitation cost.